Standard specification for Pressure Vessel Plates, Alloy Steel, Manganese-Vanadium-Nickel (American Society for Testing and Materials, 2008)
This specification covers manganese-vanadium-nickel alloy steel plates intended primarily for welded layered pressure vessels.